APPLICATION OF ARTIFICIAL INTELLIGENCE (AI) IN AGRICULTURE BY IMPLEMENTING INTERNET OF THINGS (IOT) TECHNOLOGY AND UNMANNED AERIAL VEHICLE (UAV) - Ariyani, Rizki (International Journal Science and Technology, 2024)
Smart farming is developing quite well, using Unmanned Aerial Vehicle (UAV) technology and the Internet of Things (IoT). UAVs are estimated to have ease of use, affordability so that farmers can use them. Most UAVs are controlled by remote controllers using radio waves, wireless, and bluetooth. The technology could transform traditional agricultural activities into modern activities, such as using drones for the agricultural sector. The application of this technology is done to improve the efficiency of products and the implementation of agricultural activities. Unmanned Aerial Vehicle is realized by applying artificial intelligence and human skills to precision farming.